1980
DOI: 10.1037/0033-2909.87.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavior therapy with children: Has clinical utility been demonstrated?

Abstract: Considerable attention has recently been focused on intervention techniques designed to alter cognitive processes in an attempt to modify clinically relevant child behaviors. Studies in which children have been taught cognitive mediating strategies (methods collectively known as cognitive behavior therapy) were evaluated in terms of subject populations, adequacy of outcome measures, experimental and statistical methodology, and consistency of findings. In general, deficiencies were found on all dimensions. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(24 citation statements)
references
References 88 publications
(79 reference statements)
2
22
0
Order By: Relevance
“…The current research however, appears to support previous studies which fail to indicate global improvements in maintenance and generalisation as a result of cognitive behaviour therapy (36).…”
Section: Tablesupporting
confidence: 77%
See 1 more Smart Citation
“…The current research however, appears to support previous studies which fail to indicate global improvements in maintenance and generalisation as a result of cognitive behaviour therapy (36).…”
Section: Tablesupporting
confidence: 77%
“…Statistics are shown in Table 9. The methodology employed in the present study is an improvement on that used in previous research, which has been characterized by lack of control groups and follow-up testing and the use of non-clinical samples (36,37). In addition the examined intervention aimed at improving children's overall sense of competence, differing from previous interventions which targetted explicit and isolated skills (53).…”
Section: Tablementioning
confidence: 99%
“…(Nelson & Cone, 1979) and Differential Reinforcement of Other Behavior procedures (DRO; Homer & Peterson, 1980) complained that the independent variables are not described in sufficient detail for evaluation of the results. These and other reviews (e.g., Hobbs, Moguin, Tyroler, & Lahey, 1980) have implicated the lack of independent variable description and verification as a likely cause for poor replication of results.…”
mentioning
confidence: 91%
“…One study frequendy cited or reprinted (see Abikoff, 1979;Brundage-Aguar, Forehand, & Ciminero, 1977;Hobbs, Moguin, Tyroler, & Lahey, 1980;Kendall & Finch, 1979;Meichenbaum & Asarnow, 1979;O'Leary & O'Leary, 1977;Ross, 1981) because of its success in obtaining positive generalization to classroom behavior as a result of training on psychoeducational tasks is that by Bornstein and Quevillon (1976). These authors demonstrated that the on-task behavior of three overactive preschoolers increased from a baseline level of under 20% to above 75% as a result of self-instructional training.…”
mentioning
confidence: 99%